2021
DOI: 10.1136/ejhpharm-2021-002944
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learnt from the COVID-19 pandemic: results of EAHP survey on the future crisis preparedness of hospital pharmacies

Abstract: Aim The present survey aimed to collect information on the lessons learnt from the COVID-19 pandemic by hospital pharmacists. It focused on the shortages of health goods and the experiences of hospitals during the first phase of the crisis. Methods A 17-question survey was conducted by EAHP, looking at the experiences of hospital pharmacists during the COVD-19 pandemic. The survey ran from 16 September to 23 December 2020. Statistical analysis included backward stepwise logistic regression (BSLR), Pearson's χ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Shortages of antimicrobial drugs compromise their prudent use and must be avoided. Surveys conducted by EAHP in 201932 and 202033 showed that antibiotics ranked among the top three medicinal product shortages. Measures need to be taken by countries, including national governments, the pharmaceutical industry, healthcare professionals, patients as well as other stakeholders at the pan-European level, to lower the risk of antibiotic shortages, especially since substitution supported by the AMS team is not always possible.…”
Section: Incentivesmentioning
confidence: 99%
“…Shortages of antimicrobial drugs compromise their prudent use and must be avoided. Surveys conducted by EAHP in 201932 and 202033 showed that antibiotics ranked among the top three medicinal product shortages. Measures need to be taken by countries, including national governments, the pharmaceutical industry, healthcare professionals, patients as well as other stakeholders at the pan-European level, to lower the risk of antibiotic shortages, especially since substitution supported by the AMS team is not always possible.…”
Section: Incentivesmentioning
confidence: 99%
“…Consequently, EC identified AMR as one of the top three public health threats in the European Union 4. Additionally, during the COVID-19 pandemic, 69% of 1466 hospital pharmacists experienced the most significant shortages in personal protective equipment, indicating healthcare systems’ responsibility for the extensive environmental waste and contamination that contribute to climate change 5 6. Moreover, the new medicine verification system of implementation as part of the Falsified Medicines Directive (FMD) that most affected pharmacists was established in the same year COVID-19 started 7.…”
Section: Introductionmentioning
confidence: 99%
“…This includes low-level disinfectants that can destroy bacteria and some viruses, but not bacterial spores (e.g., sodium hypochlorite) and high-level disinfectants that can also kill bacterial spores (e.g., ethylene oxide and chlorine dioxide) . Furthermore, shortages of these chemicals have become an issue in times of high demand, as experienced by hospitals during the pandemic . The use of ultraviolet (UV) radiation to inactivate pathogens has been an attractive alternative, but only surfaces exposed to the path of the UV light can be disinfected .…”
Section: Introductionmentioning
confidence: 99%
“… 11 Furthermore, shortages of these chemicals have become an issue in times of high demand, as experienced by hospitals during the pandemic. 12 The use of ultraviolet (UV) radiation to inactivate pathogens has been an attractive alternative, but only surfaces exposed to the path of the UV light can be disinfected. 13 The environmental and economic impact of healthcare waste evidenced by the pandemic has encouraged the search for alternative easy-to-use, efficient disinfection techniques.…”
Section: Introductionmentioning
confidence: 99%